Barriers to research access during COVID-19: Interviewing students with disabilities in South African higher education - Ndlovu, Sibonokuhle (Critical Studies in Teaching and Learning, 2023)
Carrying out research using face-to-face interviews with students with disabilities has been most difficult in higher education during COVID-19 pandemic. This paper seeks to answer the question: what are the barriers confronted by researchers in conducting interview research with students with disabilities in South African higher education during the COVID-19 pandemic? Data were collected by analysing and synthesising South African and international literature available in Research Gate, ERIC, JSTOR, Sabinet, ProQuest, books, journal articles, and online resources. With Critical Disability Theory illuminating the study, the major finding was that there are communication barriers when interviewing students with disabilities. The nature of the communication challenges varies from one category of disability to the other and have been exacerbated during COVID-19, thus limiting the voice of those students in research which could contribute to improvement in their learning.